2003
DOI: 10.1074/jbc.m304563200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the C-terminal 10-kDa Subdomain of Hsc70

Abstract: The 70-kDa heat shock proteins (Hsp70), including the cognates (Hsc70), are molecular chaperones that prevent misfolding and aggregation of polypeptides in cells under both normal and stressed conditions. They are composed of two major structural domains: an N-terminal 44-kDa ATPase domain and a C-terminal 30-kDa substrate binding domain. The 30-kDa domain can be divided into an 18-kDa subdomain and a 10-kDa subdomain. Here we report the crystal structure of the 10-kDa subdomain of rat Hsc70 at 3.45 Å. Its hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
55
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
10
55
0
Order By: Relevance
“…However, there was an apparent discrepancy as to the role of sub-domains, whether the client-binding sub-domain or the lid sub-domain is critical for this role. The 10-kDa C-terminal lid sub-domain (amino acids 542-646) of rat Hsc70, which forms an elongated bundle-like structure, dictates the self-association (22). In contrast, Fouchaq et al (20) reported that the 17-kDa peptide-binding sub-domain (amino acids 385-540 of Hsc70) was involved in the oligomerization process.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, there was an apparent discrepancy as to the role of sub-domains, whether the client-binding sub-domain or the lid sub-domain is critical for this role. The 10-kDa C-terminal lid sub-domain (amino acids 542-646) of rat Hsc70, which forms an elongated bundle-like structure, dictates the self-association (22). In contrast, Fouchaq et al (20) reported that the 17-kDa peptide-binding sub-domain (amino acids 385-540 of Hsc70) was involved in the oligomerization process.…”
Section: Discussionmentioning
confidence: 98%
“…According to the structure proposed by Chou et al (22), the lid sub-domain of one molecule associates with that of another molecule in an anti-parallel manner, in which 2 cysteines are separated from each other, and therefore, do not seem to form a disulfide bridge. Thus, we insist that the dimeric structure proposed by Chou et al (22) should be carefully re-investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies to pinpoint the region involved in selfassociation have focused on Hsc70 (Angelidis et al 1999;Fouchaq et al 1999;Chou et al 2003;Nemoto et al 2006;Amor-Mahjoub et al 2007). The regions essential for selfassociation of Hsc70 were found to be the conserved hydrophobic residues within the interdomain linker region and the helices at the end of the C terminus (AmorMahjoub et al 2007).…”
Section: Discussionmentioning
confidence: 99%